Intracellular pH Control by Membrane Transport in Mammalian Cells. Insights Into the Selective Advantages of Functional Redundancy - Doyen, Denis; Poët, Mallorie; Jarretou, Gisèle; Pisani, Didier F.; Tauc, Michel; Cougnon, Marc; Argentina, Mederic; Bouret, Yann; Counillon, Laurent (Frontiers in Molecular Biosciences, 2022)
Intracellular pH is a vital parameter that is maintained close to neutrality in all mammalian cells and tissues an acidic in most intracellular compartment. After having presented the main techniques used for intracellular an vesicular pH measurements we will briefly recall the main molecular mechanisms that affect and regulate intracellular pH. Following this we will discuss the large functional redundancy found in the transporters of H+ or acid-base equivalents. For this purpose, we will use mathematical modeling to simulate cellular response to persistent and/or transient acidification, in the presence of different transporters, single or in combination. We will also test the presence or absence of intracellular buffering. This latter section will highlight how modeling can yield fundamental insight into deep biological questions such as the utility of functional redundancy in natural selection